Morphological and molecular analyses of a new species of Saccocoelioides Szidat, 1954 (Haploporidae Nicoll, 1914) in the fat sleeper Dormitator maculatus (Bloch) (Perciformes: Eleotridae) from the Gulf of Mexico. Issue 4 (26th July 2016) - Andrade-Gómez, L.; Pinacho-Pinacho, C.D.; Hernández-Orts, J.S.; Sereno-Uribe, A.L.; García-Varela, M.
Abstract: Saccocoelioides olmecae n. sp. is described from specimens recovered from the intestine of the fat sleeper Dormitator maculatus (Bloch) (Perciformes: Eleotridae) collected in six localities along the coast of the Gulf of Mexico. The new species is mainly distinguished from the other three described species of Saccocoelioides Szidat, 1954 from North and Middle America (i.e. S. sogandaresi Lumsden, 1963, S. chauhani Lamothe-Argumedo, 1974 and S. lamothei Aguirre-Macedo & Violante-González, 2008) by having an elongated body, a sac-like caecum, a uterus that extends to the first third of body and by having vitelline follicles longitudinally elongated reaching the posterior end of the body. Sequences of the large subunit (LSU) of the ribosomal DNA, including the domain D1–D3, and the internal transcribed spacer 2 (ITS2) were used independently and concatenated to corroborate the morphological distinction among S. olmecae n. sp., S. chauhani and S. lamothei from freshwater and brackish-water fish from Middle America. The genetic divergence estimated among the three species of Saccocoelioides was very low: 1% for LSU and from 1 to 4% for ITS2. Maximum likelihood and Bayesian inference analyses for each dataset and both datasets combined revealed that S. olmecae n. sp. represents an independent clade with moderate bootstrap support and posterior probabilities. This is the third species of Saccocoelioides described in Mexico, and the 17th species from the Americas.